Accidentally fabulous - Papademetriou, Lisa. (New York : Scholastic, 2008)
Amy Flowers is a new seventh-grader at the super-exclusive Allington Academy. She's trying to fit in, but there's one thing standing in her way: The League. They rule the school and their leader is the oh-so-mean Fiona. If Amy can pass The League's tests, she'll be part of the popular crowd--but what will she have to give up to fit in?
"A Candy Apple book".
Keywords: Popularity -- Juvenile fiction; Cliques (Sociology) -- Juvenile fiction; Junior high school students -- Juvenile fiction